Peningkatan Kualitas Perkuliahan Etnobotani Melalui Lesson Study Pada Mahasiswa Prodi Biologi Fakultas Sains dan Teknologi Universitas Jambi: (Improving the Quality of Ethnobotany Lectures Through Lesson Study for Biology Study Program Students, Faculty of Science and Technology Jambi University ) - Ade Adriadi; Bambang Hariyadi; Revis Asra; Nanda Rayani (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2022)
This research was conducted to determine the pattern of lesson study-based learning in ethnobotany subjects so as to improve the quality of lectures for students of the Biology Study Program, FST UNJA. This research is similar to classroom action research. The research that uses the lesson study model consists of 3 stages, namely planning (planning), Do & See (Actions and Observations/Observations), and Reflection (Reflection). Improving the quality of lectures can be seen through student learning outcomes. Student learning outcomes were measured using various instruments. Assessment of student knowledge is carried out using multiple choice test questions, assessment of student skills is carried out through simplicia making project assignments, assessment of student attitudes is carried out using observation sheets, self-assessment sheets, and peer assessment sheets. The results showed that student learning outcomes have increased, namely in the first cycle of lesson study implementation, the percentage of students' classical mastery in the cognitive aspect was 70.37%, increasing to 88.88% in the second cycle. With the number of students 27 people, it is known that the average value of cognitive aspects obtained in the first cycle is 80, which increases in the second cycle to 92. Then the student activity in the first cycle and second cycle has increased at each cycle meeting where the average cycle I meeting 1 and 2 the average student activity increased from 42.19% to 58.61%, in the second cycle of meetings 1 and 2 the average student activity increased significantly from 71.65% to 83.57%. In conclusion, the quality of lectures increased after the implementation of the lesson study model. Key words: Lesson Study, Lecture Quality, Ethnobotany Abstrak Penelitian ini dilakuakn untuk mengetahui pola pembelajaran berbasis lesson study pada matakuliah etnobotani sehingga dapat meningkatkan kualitas perkuliahan bagi mahasiswa Prodi Biologi FST UNJA. Penelitian ini merupakan penelitian yang mirip dengan penelitian tindakan kelas. Pada penelitian yang menggunakan model lesson study ini terdiri dari 3 tahap yaitu planning (perencanaan), Do & See (Tindakan dan Pengamatan/Observasi), dan Reflection (Refleksi). Peningkatan kualitas perkuliahan dapat dilihat melalui hasil belajar mahasiswa. Hasil belajar mahasiswa diukur menggunakan berbagai intrumen. Penilaian pengetahuan mahasiswa dilakukan menggunakan tes soal pilihan ganda, penilaian keterampilan mahasiswa dilakukan melalui tugas proyek pembuatan simplisia, penilaian sikap mahasiswa dilakukan menggunakan lembar observasi, lembar penilaian diri, dan lembar penilaian teman sebaya. Hasil penelitian menunjukkan bahwa hasil belajar mahasiswa mengalami peningkatan yakni pada siklus I pelaksanaan lesson study di dapati persentase ketuntasan klasikal mahasiswa pada aspek kognitif sebesar 70,37% meningkat menjadi 88,88% pada siklus II. Dengan jumlah mahasiswa 27 orang, diketahui nilai rata-rata aspek kognitif yang diperoleh pada siklus I yaitu 80 meningkat pada siklus II menjadi 92. Kemudian aktivitas mahasiswa pada siklus I dan siklus II mengalami peningkatan pada setiap pertemuan persiklusnya yang mana rata-rata siklus I pertemuan 1 dan 2 rata-rata aktivitas mahasiswa 42,19% meningkat menjadi 58,61%, pada siklus II pertemuan 1 dan 2 rata-rata aktivitas mahasiswa meningkat secara signifikan dari 71,65% menjadi 83,57%. Kesimpulannya kualitas perkuliahan meningkat setelah diterapkannya model lesson study. Kata kunci: Pembelajaran daring, pandemi covid-19, biologi